Composite AI – A financial simulation: Array - Emin (Leonte), Anamaria-Nadie (Acta Universitatis Danubius. Œconomica, 2021)
Composite materials tend to increasingly replace classical materials in a wide variety of fields. The major market segments of composites are: boats, cars, heavy duty vehicles, building and constructions, sports and recreation, wind power, corrosion resist elements, aeronautics and military applications. However, there are many other very important applications and new products are released every year. There are various reasons why new materials can be favoured. Typical examples include materials which are less expensive, lighter, stronger or more durable when compared with common materials. Considering the above, but also the importance of using artificial intelligence in almost all areas of activity, the existence of software that provides numerical and graphical results on various issues in the field of composite materials can have a major financial advantage for both those who use it and for the companies that provide such services.